Terjemahan Beranotasi Dongeng La Sorcière De La Rue Mouffetard dalam Bahasa Indonesia - Everina, Rifqi Ayu; Laksman-Huntley, Myrna (UI Scholars Hub, 2022)
An annotated translation is a translation with notes or annotations of the equivalent selected in the target language with the aim of being accountable for the equivalent. This study examines a tale entitled “la Sorcière de la Rue Mouffetard” written by Pierre Gripari. This study employs qualitative methods and a comparative model to discuss translation problems and their solutions using translation strategies from Molina and Albir (2002). The use of interjection, idioms, and words containing culture is the problem in this fairy tale translation of language and cultural elements. Various dictionaries and websites are used both in the process of translating and the annotation process. The results of this study are expected to become one of the Indonesian-language fairy tales that will enrich children’s literature, especially from France.